2014
DOI: 10.1088/1742-6596/487/1/012005
|View full text |Cite
|
Sign up to set email alerts
|

Bicritical or tetracritical: the 3D anisotropic Heisenberg antiferromagnet

Abstract: Abstract.The classical uniaxially anisotropic Heisenberg antiferromagnet on the simple cubic lattice, in the presence of an external magnetic field, is believed to have a multicritical point; however, there has been controversy whether it is a bicritical or a tetracritical point. We perform Monte Carlo simulations of this model and analyze the components of the staggered magnetization, the susceptibilities and the probability distribution of the magnetization to conclude that the multicritical point is bicriti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Subsequently, a full renormalization group study of the flow equations at the multicritical point taking into account the the reversible terms concluded that in two-loop order the biconical fixed point becomes stable, whereas the Heisenberg fixed remains stable in a one-loop calculation [13]. In contrast, a series of detailed Monte Carlo simulations analyzing order parameter susceptibilities, the Binder cumulant, and associated probability distributions provided concrete evidence that the nature of the multicritical point is in fact bicritical with Heisenberg symmetry [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, a full renormalization group study of the flow equations at the multicritical point taking into account the the reversible terms concluded that in two-loop order the biconical fixed point becomes stable, whereas the Heisenberg fixed remains stable in a one-loop calculation [13]. In contrast, a series of detailed Monte Carlo simulations analyzing order parameter susceptibilities, the Binder cumulant, and associated probability distributions provided concrete evidence that the nature of the multicritical point is in fact bicritical with Heisenberg symmetry [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, it has been recently shown [4] that the multicritical point of the three-dimensional XXZ antiferromagnetic model on a cubic lattice in an external field is, in fact, despite previous debates, a bicritical point whose universality class is the same as the three-dimensional Heisenberg model. On the other hand, Andrade et al [2] have located the bicritical point on the three-dimensional anisotropic Heisenberg model in a crystal field corroborating our previous preliminary location at (D,T) = [3.95(4), 1.73 (3)] [3], where D is the crystal field in units of the exchange interaction and T is the temperature in units of the ratio of the exchange interaction and the Boltzmann constant.…”
Section: Introductionmentioning
confidence: 99%